Legal control of Public Procurement in Bosnia and Herzegovina - Romić, Marko (Glasnik Advokatske komore Vojvodine, 2024)
The article analyzes the normative framework of the legal control, both appellate and administrative, of the public procurement procedure in Bosnia and Herzegovina. Using the method of conceptual analysis, the concept of legal control of the public procurement procedure is determined in relation to other types of control. All types of legal control are restricted, thus the emphasis is placed on the appeal before the Procurement Review Body and the lawsuit in the administrative dispute. The dogmatic-normative approach to legal solutions in Bosnia and Herzegovina is complemented by comparative legal experiences and recent administrative (judicial) practice, and also by relevant legislation of the European Union. In conclusion, the author points out all the shortcomings of the legal control of the public procurement procedure with concrete proposals for improving the normative framework of public procurement in Bosnia and Herzegovina.